‘Islam’ As New Genre - Sokowati, Muria Endah (2015)
The revival of Islam in the political discourse in Indonesia after the collapse of new order period implicated in the adoption of Islamic way of life of people in every day life. This situation has brought to the production of movies containing Islamic values. The movies were successful in attracting audience and triggered the same movies produced. The emergence of special movies with Islamic content for religious marketplace-at this context, for Muslim audience-has created a new genre in movie industry during the post new order in Indonesia. As a new genre, Islamic movies were made with their generic convention, including structural codes and patterns, which build the movie texts, such as iconography, characterization, setting, dialogue type, and narration. This paper will identify and analyze what and how the generic convention consisted in Islamic movies within Indonesian context. By using genre analyses proposed by Thwaites et. al (1994), this paper will explore the structure of the texts, and link to the context, in order to describe and define the Islamic movies as new movie genre in Indonesia. According to Thwaites et. al, this analysis offered the reading of genre focusing on the textual and contextual effects. The analytical process not only reads the structure and elements of representation, but also enables to read and study the choice of subject matter contained in the movies and its relation to the social context of the process of meaning production. This paper also explains the representation of Islamic values, gender relation, and also the depiction of western culture, which often mentioned as the opposite of Islam and middle-east culture. As the conclusion, this analysis will describe on how the Islamic movies represent the face of Islam in the setting of the radical change of mediascape and political regime in Indonesia.